Influence of temperature on development of Schistosoma mansoni female cercariae in Biomphalaria glabrata Influência da temperatura sobre o desenvolvimento da cercária fêmea de Schistosoma mansoni em Biomphalaria glabrata - Cecília Pereira de Souza; Liana K. Jannotti-Passos; Sueleny Silva Ferreira; Ivan Barbosa Machado Sampaio (Revista do Instituto de Medicina Tropical de São Paulo, 1995)
In these experiments the ratio of male to female S. mansoni larvae in D. glabrata from Belo Horizonte and Ribeirão das Neves Minas Gerais, Brazil, either reared in laboratoty or collected in the field, varied from 1:1 to 1:1.3 or 1.4:1. Cercariae of LE strain of Schistosoma mansoni, shed by 39 snails maintained at 25±0.5ºC were used to infect mice on a weekly basis. Subsequent perfusion resulted in 76.6% male and 23.4% female worms. The cercariac produced by 32 infected snails maintained at 27+0.5°C were inoculated into mice and produced 43.4% male and 56.6% female worms (p<0.05). Cercariae eliminated by snails collected in Barreiro and Ressaca, Belo Horizonte, during hot months, produced 45.7 to 47.7% male and 52.3 to 54.3% female worms. A lower number of cercariae shed by snails collected in Gorduras, Belo Horizonte, at 20+3.0°C, produced 51.6% male and 48.4% female worms. Thus, in this region the infection of vertebrate hosts with S. mansoni cercariae would be more severe in the summer due to the higher level of parasites and the number of eggs. Nestes experimentos a relação de larvas de Schistosoma mansoni, macho e fêmea, em Biomphalaria glabrata de Belo Horizonte e de Ribeirão das Neves, MG, Brasil, criada no laboratório ou capturada no campo variou de 1:1 a 1: 1 ,3 ou 1,4:1. Cercánas de 39 moluscos mantidos a 25 ± 0,5°C, inoculadas em camundongos originaram 76,6% de vermes machos e 23,4% de fêmeas; cercárias de 32 exemplares mantidos a 27 ± 0,5°C, originaram 43,4% de vermes machos e 56,6% de fêmeas (p<0,05). Cercárias de moluscos capturados no Barreiro e Ressaca, Belo Horizonte, em meses quentes, originaram 45,7 a 47,7% de vermes machos e 52,3 a 54,3% de fêmeas. Moluscos capturados em meses frios (20 + 3,0°C) no Gorduras, Belo Horizonte, produziram número menor de cercárias, que originaram 51,6% de machos e 48,4% de fêmeas. Portanto, nessa região, as infecções dos hospedeiros vertebrados com S. mansoni, poderão ser mais graves no verão devido a carga parasitária e número maior de ovos.